The Effect of Information Asymmetry, Systematic Risk and Investment Opportunity (IOS) on Profit Quality in Food & Beverage - Wiwiek Winingshe (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain empirical evidence and analyze the factors that influence earnings quality. The independent variables used in this study are Information Asymmetry, Systematic Risk and Investment Opportunity Set (IOS). The dependent variable in this study is earnings quality. The population used in this study are Manufacturing Companies in the Food & Beverage Sub-Sector Registered on the Indonesia Stock Exchange (IDX) from 2013 to 2022. Design/methodology/approach – The research method used is descriptive quantitative. The type of data used is secondary data in the form of published financial reports of manufacturing companies in the food & beverage sub-sector which are listed on the Indonesia Stock Exchange in 2013-2022. Samples were collected by purposive sampling method. The number of companies that were sampled in this study were 10 companies with a research period of 10 years. Data processing using SPSS version 20 for windows by collecting related data and then calculating information asymmetry, systematic risk, and Investment Opportunity Set (IOS) and earnings quality. T), and multiple linear regression test Findings – The results of this study partially show that information asymmetry has no effect on earnings quality, systematic risk has a negative and significant effect on earnings quality, Investment Opportunity Set (IOS) has a positive and significant effect on earnings quality. Simultaneous test results show that information asymmetry, systematic risk, and Investment Opportunity Set (IOS) affect earnings quality.